Pembuatan Bibit Jamur Tiram Putih dengan Melibatkan Remaja di Desa Situ Ilir - . Mursyidah; Lusia Anita Boru Sagala; Maya Risanti; . Irzaman; Mersi Kurniati (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2015)
The community service activities to develop practical skill of teenager on seedling production of oyster mushroom (Pleurotus ostreatus) through counseling and training at Situ Ilir Village. This training was begin with counseling followed by training for seedling production of pure culture (F0), spread seeds (F1), and planting seeds (F2). The quality of this training was assured by comprehensive monitoring and evaluation. In each step of seedling production, variations of sterilization medium were used and was then analyzed using Fourier Transform Infrared Spectroscopy (FTIR) analysis. The characterization results using FTIR shows stretching vibration in mycelium for pure culture and planting seeds. The stretching vibration identify the presence of several functional of groups C-O, C-N, C=O, C-H, O-H, and β-D-glucan. The results of this training also shows that after several practice and intensive guidance the teenager were able to produce seeds of oyster mushroom (Pleurotus ostreatus) without supervision.